Ferroelectric and electrical characterization of multiferroic BiFeO3 at the single nanoparticle level - Vasudevan, R. K.; Bogle, Kashinath A.; Kumar, A.; Jesse, S.; Magaraggia, R.; Stamps, R.; Ogale, Satishchandra B.; Potdar, H. S.; Nagarajan, V. (Applied Physics Letters, 2011)
Ferroelectric BiFeO3 (BFO) nanoparticles deposited on epitaxial substrates of SrRuO3 (SRO) and La1-xSrxMnO3 (LSMO) were studied using band excitation piezoresponse spectroscopy (BEPS), piezoresponse force microscopy (PFM), and ferromagnetic resonance (FMR). BEPS confirms that the nanoparticles are ferroelectric in nature. Switching behavior of nanoparticle clusters were studied and showed evidence for inhomogeneous switching. The dimensionality of domains within nanoparticles was found to be fractal in nature, with a dimensionality constant of similar to 1.4, on par with ferroelectric BFO thin-films under 100 nm in thickness. Ferromagnetic resonance studies indicate BFO nanoparticles only weakly affect the magnetic response of LSMO. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3671392]